Pengaruh Gender Diversity, Risk Minimization dan Agresivitas Pajak terhadap Corporate Social Responsibility - Syifa Aulia; Fikriyah, Siti Hailatul (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
This research aims to find out and provide empirical evidence regarding Gender Diversity, Risk minimisation, and Tax Aggressiveness towards Corporate Social Responsibility in Non-Cyclical Consumer Sector Companies listed on the Indonesian Stock Exchange for the 2018-2023 period. This type of research is used in quantitative research. The number of samples in this study was as large as 72 observational data from 125 non-cyclical consumer companies for the 2018-2023 period, which was obtained using a purposive sampling method based on established criteria. The data used is secondary data, namely in the form of annual reports and sustainability reports for the 2018-2023 period, obtained from the official website of the Indonesian Stock Exchange. The technical data analysis used is descriptive statistics and panel data regression analysis using EViews 12 software. The results of this research are based on tests simultaneously stating that Gender Diversity, Risk Minimisation, and Aggressiveness Taxes have a simultaneous effect on Corporate Social Responsibility. Based on the partial test, it states that Gender Diversity and Tax Aggressiveness influence Corporate Social Responsibility. Meanwhile, Risk minimisation has no effect on Corporate Social Responsibility.